Estimating the availability of hydraulic drive systems operating under different functional profiles through simulation - Reed, Sean; Löfstrand, Magnus (Taylor & Francis, 2016)
Hydraulic drive systems are widely used in a variety of industrial applications where high torque and low speed rotational power are required. The advantages include maximum torque from zero speed, continuously variable speed within wide limits, high reliability and insensitivity to shock loads. A drive system consists of a hydraulic circuit, electric motors, hydraulic pumps, hydraulic motors and auxiliary components. The stress on the components, and hence wear and failure rate, varies with the torque and speed output by the drive. The reliability of a hydraulic drive system of a particular design can therefore vary significantly between installations operating in applications with different functional requirements. Predicting the availability of a drive system in a particular application is useful for several purposes such as optimising the system design and estimating support costs. This paper describes a simulation model, developed to estimate the availability of a hydraulic drive system in a given functional profile, consisting of output torque and speed time phase requirements. It outputs statistics on system availability and component failure rates. As an example, the simulation model is used to compare these statistics for a drive design operating under two distinct operational profiles.